Philosophical Basis of Informed Consent, Informed Refusal and Documentation of Medical Information into Medical Record - Yuni Lestari, Ahdiana; Jenie, Ismijatie (Jurnal Media Hukum, 2019)
Information delivered by the medical professionals to the patients in their initial communication is crucial in establishing the therapeutic contract (transaction). Based on that information, the patient will decide whether to accept or to refuse the proposed medical treatment. This paper discusses the philosophical basis of the Informed Consent, Informed Refusal and the documentation of medical information into Medical Record. This normative legal research is carried out by library-based study on primary and secondary legal materials. Besides descriptive-analytical approach, the study also employs comparative approach. The comparison is made between continental legal system, common law system, and the Islamic legal system. It is found that philosophical basis of informed consent, informed refusal and documentation of medical information into medical record is basically to protect the patients’ dignity and to maintain their trust and cooperation. Furthermore, from the Islamic perspective the establishment of informed consent is to respect the privacy to blood, property, and family. In addition, the documentation of medical information into the medical record is to give legal protection in the form of strong evidence both for the health providers and health receivers in the event of a medical dispute.